2022
DOI: 10.1590/fst.57822
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and antitumor activities of the exopolysaccharide produced by potential probiotic Lactobacillus plantarum YW11 in a HT-29 tumor-burdened nude mouse model

Abstract: In this study, the exopolysaccharides (EPSs)-producing L. plantarum YW11 was initially evaluated for its tolerance to simulated artificial gastric juice and bile salts, and cell surface hydrophobicity. Subsequent study using a HT-29 tumor-burdened nude mouse model showed that the EPS had potent immunomodulatory and antitumor activities. Administration of the EPS had no influence on body weight of the mice, and it could significantly prevent HT-29 tumor cells induced acute liver and kidney damages. The purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…It can compete for IL-2 binding with the membrane interleukin-2 receptor (mIL-2R). Neutralize activated T cells and surrounding IL-2, operate as blocking factors, restrict T cell growth, and impair immunological activity in the body (Zhang et al, 2022). IFN-γ is a glycoprotein with significant immunomodulatory properties that can increase cellular performance, speed up immunological complex clearance, and improve phagocytic foreign body function, as well as having a bidirectional regulatory influence on lymphocytes (Shao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It can compete for IL-2 binding with the membrane interleukin-2 receptor (mIL-2R). Neutralize activated T cells and surrounding IL-2, operate as blocking factors, restrict T cell growth, and impair immunological activity in the body (Zhang et al, 2022). IFN-γ is a glycoprotein with significant immunomodulatory properties that can increase cellular performance, speed up immunological complex clearance, and improve phagocytic foreign body function, as well as having a bidirectional regulatory influence on lymphocytes (Shao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The exopolysaccharides (EPSs)-producing L. plantarum YW 11 has potent immunomodulatory and antitumor activities. EPS prevented HT-29 tumor cells induced acute liver and kidney damages significantly, and promoting secretion of cytokines IL-2 and TNF-α in mice (Zhang et al, 2022). Lactobacillus plantarum SCS2 obviously protected against AFB1-induced oxidative stress.…”
Section: Introductionmentioning
confidence: 89%
“…The results showed that L. plantarum YW11 is able to convert LA into a CLA isomer (rumenic acid) and stearic acid, at different concentrations of LA (also in this case1-10 % w/v) [121]. L. plantarum YW11, isolated from kefir from Tibet, has been found to possess antimicrobial, anticancer, antioxidant, and immuno-regulatory activities [136,137].…”
Section: In Vitro Cla Production By L Plantarummentioning
confidence: 95%